2017
DOI: 10.32404/rean.v4i5.2188
|View full text |Cite
|
Sign up to set email alerts
|

Diferentes Doses E Épocas De Aplicação De Zinco Na Cultura Da Soja

Abstract: A soja é uma das culturas mais importantes do mundo sendo sua produtividade afetada pela deficiência do micronutriente zinco. O presente trabalho teve como objetivo avaliar o efeito de doses e épocas de aplicação de zinco nas características agronômicas da soja, cultivada em solo da região do Cerrado. O delineamento experimental utilizado foi o de blocos casualizados em esquema fatorial 2 x 5, sendo, duas épocas de aplicação (estádio V9 e R1) e cinco doses (0, 3, 6, 9 e 12 kg ha-1 de zinco), com quatro repetiç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
1
5
1
6
Order By: Relevance
“…The Zinc treatments significantly increased all vegetative parameters evaluated compared to the non-inoculated control (Table 3), corroborating Oliveira et al (2017), who observed a positive influence of soybean fertilization with Zn on vegetative and productive parameters.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The Zinc treatments significantly increased all vegetative parameters evaluated compared to the non-inoculated control (Table 3), corroborating Oliveira et al (2017), who observed a positive influence of soybean fertilization with Zn on vegetative and productive parameters.…”
Section: Resultssupporting
confidence: 85%
“…In a study by Oliveira et al (2017) they observed that Zn application promoted increase in plant height, shoot dry mass and soybean root mass, with the highest averages observed for the higher doses of Zn. The results also corroborate the present study (Table 5).…”
mentioning
confidence: 99%
“…In soybean cultivated in soil from the Cerrado region of Brazil, Oliveira et al (2017) observed that the application of Zn via soil (0, 3, 6, 9 and 12 kg ha -1 of Zn) during phenological stage V9 (eighth fully developed trifoliate leaf) linearly increased leaf Zn concentration, thousand grain mass and grain yield.…”
Section: Grain Yield and First Pod Insertion Heightmentioning
confidence: 97%
“…Development, v. 9, n. 7, e827973544, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.3544 incorporado, semente e foliar) na cultura do trigo, observaram que a aplicação via foliar foi a que ocasionou maior acúmulo de Zn na matéria seca. Por outro lado, Oliveira et al (2017) recomendaram a adubação de Zn via solo para a cultura da soja, uma vez que os resultados da adubação afetaram positivamente o teor foliar deste micronutriente, a altura de plantas, número de vagens, nós reprodutivos, diâmetro de caule e a massa de 1000 grãos.…”
Section: Fertilização Com Zn Nas Culturas Agrícolasunclassified